Gastrointestinal sensitivity and gastroesophageal reflux disease. (11th October 2013) - Altomare, Annamaria; Luca Guarino (Sara Emerenziani), Michele Pier; Cicala, Michele; Drewes, Asbjørn Mohr; Krarup, Anne Lund; Brock, Christina; Lottrup, Christian; Frøkjær, Jens Brøndum; Souza, Rhonda F.; Nardone, Gerardo; Compare, Debora
Abstract : This paper reports on gastrointestinal sensitivity, including on the role of refluxate volume on the perception of reflux symptoms; experimental pain models that mimic mechanisms and symptoms of pain associated with esophageal diseases; the potential role of the acid receptor TRPV1 in the genesis of gastroesophageal reflux disease (GERD) symptoms; and roles for ATP and the purine and pyrimidine receptor subfamilies P1, P2X, and P2Y in the pathogenesis of GERD symptoms.